Sustained MRD negative remission in del17p and TP53 mutated B cell prolymphocytic leukemia with ibrutinib and venetoclax. (2021) - Siddiqui, Maria Tariq; Price, Allyson; Ferrajoli, Alessandra; Borthakur, Gautam
Abstract: B cell prolymphocytic leukemia is a rare and aggressive disorder often with high risk features including TP53 mutation, deletion 17p and complex karyotype. There is scarcity of data regarding treatment and existing therapies induce short lived remissions. Ibrutinib, a Bruton tyrosine kinase inhibitor, has had success in some patients with high risk features. Venetoclax, a BCL-2 inhibitor, has primarily been used in the relapsed setting. We present a case of B PLL with deletion 17p and mutated TP53 treated with ibrutinib and venetoclax in the frontline setting which resulted in measurable/minimal residual disease negative remission for approximately three years.